European muslims and their foreign policy interests: identities and loyalties - Ajala, Imène (Islam and international relations series, 2018)
In a global context marked by terrorist threats, Muslim communities in the West have come under increasing scrutiny. Sensitive questions on identity arise with regard to their foreign policy interests and their loyalties. Topics covered include:- Relations between European Muslims and international issues- Political opportunity structures- Organization and institutionalization of Islam- Diaspora and transnational dimensions- The securitization of Islam- Foreign policy and loyaltyThis book investigates the foreign policy interests and political mobilization of Muslims in Europe, specifically in France and Great Britain, contributing to shed light on these difficult questions